Lipofibromatous Hamartoma of the Median Nerve - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Lipofibromatous hamartoma is a rare tumor-like overgrowth of fibroadipose tissue surrounding the nerves. Most commonly, it involves the median nerve. The tumor is usually present at birth and grows very slowly. The expected age of clinical presentation is the third or fourth decades of life. The case reported here had a rapid overgrowth and presented at the age of eight. Our case is the first reported case of lipofibromatous hamartoma of the median nerve in the pediatric age group.
Keywords: lipofibromatous hamartoma; fibrolipomatous hamartoma; neural lipofibroma; perineural lipoma; median nerve; pediatric